СHOICE OF ZOFENOPRIL AND HYDROCHLOROTHIAZIDE COMBINATION IN THE TREATMENT OF ARTERIAL HYPERTENSION - N. A. Dzhaiani (Столичная издательская компания, 2016)
Problems of antihypertensive therapy are discussed in the light of the present epidemiological situation with arterial hypertension. ACE inhibitors have a special place among the antihypertensive drugs. Advantages and evidence base of ACE inhibitors representative - zofеnopril highlighted. Special attention is given to combined antihypertensive therapy , particularly combination of zofenopril and hydrochlorothiazide.